1983
DOI: 10.1002/chin.198320011
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: CRYSTAL STRUCTURE OF ND2ALO3N. DETERMINATION OF THE OXYGEN‐NITROGEN ORDER BY NEUTRON DIFFRACTION

Abstract: Das Oxidnitrid Nd2AlO3N wurde aus gepreßten stöchiometrischen Pulvermischungen von NdzOa und AlN durch mehrfaches Erhitzen (1350°C) und Vermahlen hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…There are relatively few examples of RP oxynitrides (Fuertes, 2010). The K 2 NiF 4 structure type ( n =1) has been reported for Nd 2 AlO 3 N (Marchand et al , 1982), Sr 2 TaO 3 N, Ba 2 TaO 3 N, Ca 2 TaO 3 N (Pors et al , 1991; Diot et al , 1999), and Sr 2 NbO 3 N (Tobías et al , 2001). The n =2 RP structure type has been reported only for Li 2 LaTa 2 O 6 N (Esmaeilzadeh et al , 2000) and Sr 3 Nb 2 O 4.7 N 2 (Tobías et al , 2001).…”
Section: Introductionmentioning
confidence: 83%
“…There are relatively few examples of RP oxynitrides (Fuertes, 2010). The K 2 NiF 4 structure type ( n =1) has been reported for Nd 2 AlO 3 N (Marchand et al , 1982), Sr 2 TaO 3 N, Ba 2 TaO 3 N, Ca 2 TaO 3 N (Pors et al , 1991; Diot et al , 1999), and Sr 2 NbO 3 N (Tobías et al , 2001). The n =2 RP structure type has been reported only for Li 2 LaTa 2 O 6 N (Esmaeilzadeh et al , 2000) and Sr 3 Nb 2 O 4.7 N 2 (Tobías et al , 2001).…”
Section: Introductionmentioning
confidence: 83%
“…Here, the valence of the anion site approximately matches the bond strength sum b at O1 (4×A−O and 2×B−O) and O2 (5×A−O and 1×B−O) defined as b O1 =4 z A / v A +2 z B / v B and b O2 =5 z A / v A + z B / v B ( z =formal valence, v =coordination number). Sr 2 TaO 3 N and Sr 2 CoO 3 F have ( b O1 , b O2 )=(2.56, 1.94) and (1.89, 1.61), implying the occupation of N/F at the O1/O2 site . Interestingly, this rule does not hold in oxyhydrides: Sr 2 VO 3 H (1.89, 1.61), LaSrCoO 3 H 0.7 (1.68, 1.67), and LaSrMnO 3.3 H 0.7 (1.88, 1.77).…”
Section: Figurementioning
confidence: 99%
“…Since the A cation in A 2 BO 3 X is in general more electropositive, there is a tendency that a more/less electronegative anion occupies the O1/O2 site . Such anion order is often encountered in oxyfluorides with F − at the axial site (Sr 2 CoO 3 F, Sr 2 NiO 3 F), in oxynitrides with N 3− at the equatorial site (Sr 2 TaO 3 N, Sr 2 NbO 3 N), though few exceptions like Nd 2 AlO 3 N exist . Given the electronegativity of H (2.2), H − is likely to occupy the O1 site, which is what has been observed previously in Sr 2 VO 3 H, LaSrCoO 3 H 0.7 , and now in LaSrMnO 3.3 H 0.7 .…”
Section: Figurementioning
confidence: 99%
“…12 In this family, the average formal oxidation state for niobium could be tuned according to the N/O ratio or/and the presence of anion vacancies, but magnetic susceptibility measurements for samples synthesized under different conditions did not show any superconducting transition down to 4 K. Oxynitride perovskites have been investigated by several groups. Marchand et al reported perovskites of early transition metals such as Ti(IV) (LaTiO 2 N), 13 Nb(V) (SrNbO 2 N), 11 Ta(V) (SrTaO 2 N), 11 and W(VI) (Sr,La)-WO 2-x N 1+x ), 14 as well as K 2 NiF 4 -type phases for Nd 2 AlO 3 N 15 and Sr 2 TaO 3 N. 16 More recently, Jansen et al investigated tantalum oxynitride perovskites (La 1-x Ca x TaO 2-x N 1+x ) with application as new nontoxic inorganic pigments. 17 One of the topics attracting much attention in these compounds as well as in other oxynitrides is the order/disorder scheme followed by the two anions on the available crystallographic sites, because this can affect properties including anionic conductivity, electrical properties, metallic conductivity, lithium intercalation capacities, etc., and the driving forces determining the anion distribution have not been completely understood.…”
Section: Introductionmentioning
confidence: 99%